Caretakers' perspectives of paediatric TB and implications for care-seeking behaviours in Southern Mozambique. - Carolina Mindu (PLoS ONE, 2017)
Tuberculosis (TB) remains an important public health concern, especially in poorly resourced settings. TB diagnosis is challenging, particularly for children, who are the most vulnerable to its' impacts. Lack of knowledge and awareness of the disease compromises prompt diagnosis and treatment compliance.To gain insights regarding caretakers' knowledge of the aetiology and prevention of paediatric TB in southern Mozambique, to describe their care-seeking behaviours and to assess the acceptability of diagnostic procedures.A total of 35 caretakers were interviewed, all of which had children with TB compatible symptoms. Eleven were caretakers of children diagnosed with TB at the health facility, 11 of children for whom TB was excluded as a diagnosis at the health facility and 13 of children with TB compatible symptoms identified in the community. The first two groups took part in a TB incidence study, while the third group did not. All underwent the same semi-structured interviews, the results of which were analysed and compared using content analysis.Even when confronted with signs suggestive of TB, most caretakers never suspected it or misinterpreted the signs, even among caretakers with TB and TB contacts. There was limited knowledge of TB, except among those undergoing treatment. The transgression of social norms was often presented as an explanation for TB in parallel to medically sound causes. The use of traditional care for prevention is widespread, but it varied for treatment purposes. TB diagnostic procedures were considered painful but were unanimously tolerated.Misconceptions of paediatric TB, associated complex care-seeking itineraries and negative feelings of the diagnostic procedures may result in delays, low adherence and lost to follow-up, which needs to be addressed by adequately framed health promotion approaches.